(untitled) (Journal of Atomic and Molecular Sciences, 2021)
By using ab initio method and elastic scattering Green’s function theory, the electronic transport properties of symmetric tetraphenyl and non-symmetric diblock dipyrimidinyldiphenyl molecules covalently bonded to two electrodes are investigated. The numerical results show that, the tetraphenyl molecule has better electronic conductivity than the diblock molecule. The latter exhibits pronounced rectification behavior. Those molecular orbitals of the tetraphenyl molecule delocalized into two gold electrodes simultaneously result in better electronic conductivity. However, the non-symmetric structure of the diblock molecule leads to the localization of molecular orbitals, which is a disadvantage to electronic transport.